2007
DOI: 10.1007/s10340-007-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

The biological efficacy of pear ester on the activity of Granulosis virus for codling moth

Abstract: Ethyl (E,Z)-2,4-decadienoate (pear ester) is an adult and larval kairomonal attractant for Cydia pomonella (L.) (Lepidoptera: Tortricidae). The possibility of using a microencapsulated formulation of pear ester (DA-MEC, a.i. 5%, Trécé Inc.) to interfere with the host location behaviour was evaluated. Laboratory leaf disc bioassays and field efficacy trials were carried out on apple to determine the potential of improving the insecticidal performance of the granulovirus of C. pomonella (CpGV) by co-mixing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…More recently, the use of pear ester plus acetic acid was found to be an effective non-pheromone lure that can enhance growers' ability to monitor female moths (Landolt et al 2007;Knight 2010). The attraction of C. pomonella larvae to pear ester has been used to improve the efficacy of some insecticides by increasing wandering time and exposure to residues prior to fruit penetration (Arthurs et al 2007;Light 2007;Schmidt et al 2008;Light and Beck 2010).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of pear ester plus acetic acid was found to be an effective non-pheromone lure that can enhance growers' ability to monitor female moths (Landolt et al 2007;Knight 2010). The attraction of C. pomonella larvae to pear ester has been used to improve the efficacy of some insecticides by increasing wandering time and exposure to residues prior to fruit penetration (Arthurs et al 2007;Light 2007;Schmidt et al 2008;Light and Beck 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of α-farnesene slightly improved the effect of CpGV (Ballard et al 2000b), pear ester reduced injury in walnuts (Light and Knight, 2011), but not in apple and pear (Arthurs et al, 2007;Schmidt et al, 2008).…”
Section: Enhancing the Effect Of Codling Moth Granulovirus (Cpgv)mentioning
confidence: 92%
“…Efforts to improve the performance of CpGV have attempted to increase virus exposure and ingestion through attractants and feeding stimulants, before larvae penetrate the fruit Ballard et al 2000a,b). However, plant volatiles which attract codling moth neonates (Sutherland and Hutchins, 1972;Knight and Light, 2001) or larval feeding stimulants, molasses or sugars, have shown only limited or no effect (Ballard et al, 2000b;Arthurs et al, 2007;Schmidt et al, 2008;Light and Knight, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In general, pear ester significantly improved the performance of synthetic insecticides with residual effectiveness and also reduced nut injury by the navel orangeworm, Amyelois transitella Walker, in walnut (Light and Knight 2011). Results with pear ester in both laboratory and field trials with insecticides requiring ingestion even when used with purported feeding stimulants have been more variable (Arthurs et al 2007b;Schmidt et al 2008;Light and Knight 2011;Knight and Witzgall 2013;Knight et al 2015).…”
Section: Insecticide Use In Organic Tree Fruit Productionmentioning
confidence: 95%
“…A second approach to improve the performance of CpGV has been the addition of feeding stimulants, and have included sugary baits, non-nutritive sugar substitutes, that is monosodium glutamate, and the amino acid, L-aspartate (Ballard et al 2000a,b;Brown 2002, 2004;Arnault et al 2016). Results from several studies examining the potential of using pear ester in both apple and pear to enhance CpGV have been inconsistent (Arthurs et al 2007b;Schmidt et al 2008;Knight et al 2015). However, field studies showed that the activity of CpGV could be enhanced by adding either the common brewer yeast Saccharomyces cerevisiae Meyen ex E. C. Hansen, or one of several yeasts isolated from field-collected larvae in combination with brown cane sugar (Knight and Witzgall 2013;Knight et al 2015).…”
Section: Insecticide Use In Organic Tree Fruit Productionmentioning
confidence: 99%